Penerapan Model Pemilihan Kartu (Card Short) Dalam Pembelajaran Fiqih Untuk Meningkatkan Keaktifan Dan Prestasi Belajar Siswa Siswa Kelas V C MIN 2 Indragiri Hulu - Ningsiah, Ningsiah (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to increase student achievement in class V C MIN 2 INHU in the subject of Jurisprudence through a card sort model, and this research uses CAR research methods or class action research (classroom action research). with the learning model type sorting cards (card sort) managed to improve student achievement. In cycle 1 students of class V C obtained an average score of 71.72 with the lowest score being 60 and the highest score being 95. There were also 17 students who had not yet reached the KKM with a classical completeness score of only 41%. In cycle II the average score was 79.82, the lowest score was 70 and the highest score was 100. Meanwhile, there were only 4 students who had not reached the KKM with classical completeness of 88%. succeeded in increasing the activity and achievement of student learning. This can be seen in the development of each cycle that is held. Namely in cycle 1 only 41% and increased in cycle II 86%. Based on the average value per cycle which is in the very good category